A within‐subject consideration of the psychotic spectrum disorder concept in a patient in remission associated with cortical gray matter recovery. (12th June 2018) - Meltzer, Herbert Y.; Sim, Min Young; Anderson, Adam; Cannistraci, Christopher; Jayathilake, Karu; Share, Daniel Barrett; Lee, Myung
Summary: Introduction: Psychotic spectrum disorder (PSD) links the syndromes of bipolar disorder, psychotic depression, and schizophrenia, often viewed as unique disorders. Aims: Application of the PSD concept to a single patient rather than across groups of patients and demonstration of a remarkable remission of schizophrenia phenotype with recovery of gray matter in specific brain regions. Results: We report a woman who experienced discrete, nonoverlapping periods of each of the above syndromes, in the order noted, over a 30‐year period, followed by abrupt ending of psychosis and full remission lasting at least 7 years. This patient had 2 episodes of Bipolar 1 mania, followed by a 20‐year period of psychotic depression. From ages 35‐48, she manifested severe, paranoid schizophrenia with marked functional decline. She became refractory to antipsychotic drugs, including oral risperidone and clozapine. At age 48, while participating in a double‐blind, 6‐month clinical trial of long‐acting injectable risperidone (Consta®, 100 mg IM biweekly) for treatment‐resistant schizophrenia, at week 23, upon awakening, complete disappearance of psychosis and marked improvement in function was noted, which persisted until the present (approximately 7 years). Remarkably, cognitive test performance in most domains improved beginning at 6 weeks and reached normal levels in executive function, despite minimal improvement in psychosis until week 23. MRI studies before and after remission revealed unique and substantial increases in gray matter of the cingulate and parietal cortex, and subthalamic nucleus, not seen in other patients in this study. Conclusions: The 3 discrete periods of psychopathology support the diagnosis of PSD. The unusual course and outcome, including remarkable improvement, in executive function and enhanced cortical gray matter in selective brain regions may have been the result of unique endogenous genetic and epigenetic factors and effect of medication.